2022
DOI: 10.3390/ani12040420
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Metabolic Profiles of Embryonic Skeletal Muscle from Lantang and Landrace Pigs

Abstract: Elucidation of the complex regulation of porcine muscle development is key to increasing pork output and improving pork quality. However, the molecular mechanisms involved in early porcine embryonic muscle development in different pig breeds remain largely unknown. Here, GC–MS based metabolomics and metabolomic profiling was used to examine the longissimus lumborum (LL) of the Lantang (LT) and the Landrace (LR) pig at embryonic day 35 (E35). Metabolites showed clear separation between LT and LR, with 40 metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Metabolomic studies should be carried out to characterize cultivated meat cell lines because the requirements of different cell types vary by species, breed, and cell line. Several studies have shown that different breeds of pigs have different metabolic profiles (Cai et al., 2022), which in turn affects cellular metabolic processes like proliferative capacity (X. ‐Q.…”
Section: Studying Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolomic studies should be carried out to characterize cultivated meat cell lines because the requirements of different cell types vary by species, breed, and cell line. Several studies have shown that different breeds of pigs have different metabolic profiles (Cai et al., 2022), which in turn affects cellular metabolic processes like proliferative capacity (X. ‐Q.…”
Section: Studying Metabolismmentioning
confidence: 99%
“…However, this may require creating alternate genome‐scale models because different breeds of the same organism have different metabolic requirements. For example, it is possible to differentiate between Lantang and Landrace pigs using metabolomics because 40 metabolites in Lantang pigs have a higher abundance than in Landrace pigs (Cai et al., 2022), and the cells derived from these two pig breeds have different proliferative capacities (X.‐Q. Wang et al., 2012).…”
Section: Gaps In Knowledge and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation